Experimental Analysis of Aluminum Alloy under Solid Particle Erosion Process - Chowdhury, Mohammad Asaduzzaman; Debnath, Uttam K.; Nuruzzaman, D. M.; Islam, Md. Monirul (SAGE Publications, UK, 2016)
The erosion behaviors of aluminum alloy have been evaluated practically at different test conditions under ambient temperature. Irregular silica sand (SiO2) is used as an erodent within the range of 300–600 mm. The impact velocity within 30–50 m/s, impact angle 15–90o, and stand-off distance 15–25 mm considered as related parameters. The maximum level of erosion is obtained at impact angle 15o which indicates the ductile manner of the tested alloy. The higher the impact velocity, the higher the erosion rate as almost linear fashion is observed. Mass loss of aluminum alloy reduces with the increase of stand-off distance. A dimensional analysis, erosion efficiency (η) and relationship between friction and erosion indicate the prominent correlation. The test results are designated using Taguchi’s concept to ensure the minimization of observations for clarification of results in alternative process. ANOVA data analysis is considered to signify the interaction of tested parameters as well as identifying most influencing operating parameter. S/N ratio indicates that there are 2.92% deviations estimated between predicted and experimental results. To elaborately analyze the results, GMDH method is mentioned. After erosion process of the tested composite, the damage propagation on the surfaces is examined using SEM for confirming wear mechanisms. The elemental composition of eroded test samples at varying percentage of aluminum is analyzed by energy dispersive X-ray spectroscopy analysis.